Memantine-Induced Liver Injury With Probable Causality as Assessed Using the Roussel Uclaf Causality Assessment Method (RUCAM). Issue 8 (27th August 2019) - Shumar, John; Ordway, Sarah; Junga, Zachary; Sadowski, Brett; Torres, Dawn
ABSTRACT: Presentations of drug-induced liver injury (DILI) are highly variable. Although biochemical evidence of cholestasis is common, the extent of aminotransferase elevations and patterns of liver injury vary. Patients may be asymptomatic, and many cases may never be diagnosed. We describe a case of memantine-induced hepatotoxicity in an elderly patient with Alzheimer's dementia, with probable causality for drug-induced liver injury, as assessed using the Roussel Uclaf Causality Assessment Method (RUCAM) score.